The Role of Estrogen Receptors in Urothelial Cancer - Goto, Takuro; Miyamoto, Hiroshi (Frontiers in Endocrinology, 2021)
Epidemiological data have indicated that there are some sex-related differences in bladder cancer. Indeed, the incidence of bladder cancer in men has been substantially higher than that in women throughout the world, while women tend to have higher stage disease and poorer prognosis. These gender disparities have prompted to investigate sex hormones and their cognitive receptors in bladder cancer. Specifically, estrogen receptors, including estrogen receptor-α and estrogen receptor-β, have been shown to contribute to urothelial carcinogenesis and cancer progression, as well as to modulating chemosensitivity in bladder cancer, although conflicting findings exist. Meanwhile, immunohistochemical studies in surgical specimens have assessed the expression of estrogen receptors and related proteins as well as its associations with clinicopathologic features of bladder cancer and patient outcomes. This review article summarizes and discusses available data indicating that estrogen receptor signaling plays an important role in urothelial cancer.